Lex Mercatoria: Study Material - Prostor, Jerneja (2016)
This study material is designed to provide sets of case studies for the course Lex mercatoria of Law 2nd bologna degree study. At the beginning of every set of case study students are directed to repeat the theoretical knowledge on the certain topic. In addition, they are provided with some practical cases, by solving which they are enabled to examine, whether they understood the lectures correctly. When working on those cases students are expected to use the Obligations Code, United Nations Convention on Contracts for the International Sale of Goods (CISG), lex mercatoria and both domestic as well as foreign case law. References to the sources of these cases and the literature, which is to be used in the study, are listed at the single task and also at the end of this study material. It consists of case studies on the following topics: formation of a contract, hardship and force majeure, limitation and exclusion of the liability for damages, penalty clause, bank guarantee, documentary credit, application and remedies for breach of contract under the CISG.